2012
DOI: 10.5194/bg-9-3943-2012
|View full text |Cite
|
Sign up to set email alerts
|

Cajander larch (<i>Larix cajanderi</i>) biomass distribution, fire regime and post-fire recovery in northeastern Siberia

Abstract: Abstract. Climate change and land-use activities are increasing fire activity across much of the Siberian boreal forest, yet the climate feedbacks from forest disturbances remain difficult to quantify due to limited information on forest biomass distribution, disturbance regimes and post-disturbance ecosystem recovery. Our primary objective here was to analyse post-fire accumulation of Cajander larch (Larix cajanderi Mayr.) aboveground biomass for a 100 000 km 2 area of open forest in far northeastern Siberia.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 63 publications
5
36
0
Order By: Relevance
“…The study was conducted in northeastern Siberia, in the Sakha Republic of the Russian Federation. The study site was located in a previously identified fire scar (Figure 1) [Berner et al, 2012] on the eastern bank of the Kolyma River in close proximity to Ambarchik Bay on the Arctic Ocean (69.47°N, 162.18°E). The area is characterized by a cold, dry climate.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in northeastern Siberia, in the Sakha Republic of the Russian Federation. The study site was located in a previously identified fire scar (Figure 1) [Berner et al, 2012] on the eastern bank of the Kolyma River in close proximity to Ambarchik Bay on the Arctic Ocean (69.47°N, 162.18°E). The area is characterized by a cold, dry climate.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Recent observations of increased fire frequency and unusually large fires [Jones et al, 2009[Jones et al, , 2013 in arctic tundra indicate that fire is becoming an increasingly important component of these ecosystems. Fire is widely recognized as an integral component of boreal forests, where it exerts strong influence on ecosystem structure [Goetz et al, 2007;Alexander et al, 2012;Berner et al, 2012] and function [Mack et al, 2008;Johnstone et al, 2010]. Changing boreal fire regimes [Kasischke and Turetsky, 2006;Kelly et al, 2013] are resulting in ecosystem changes that are likely to act as climate feedbacks [Randerson et al, 2006;Beck et al, 2011;Jin et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Scorch marks on remaining logged stumps indicate that the sites must have been burnt after this logging event, but no other burned wood was found, thus we cannot make assumptions on the pre-fire stand structure or fire frequency. Berner et al (2012), however, showed evidence for fires in the 1970s in the larger area. At the RB site, new land became available for forest colonisation ~60 years ago.…”
Section: Stand Structure Is Influenced By Disturbance Regime and Intementioning
confidence: 99%
“…Alexander et al 2012;Berner et al 2012Berner et al , 2013. Our analyses were conducted along a latitudinal gradient in the lower Kolyma river area, where Larix cajanderi Mayr is the only tree taxon.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in satellite remote sensing, such as NASA's new Global Ecosystem Dynamics Investigation Lidar (GEDI) instrument, are anticipated to help overcome some of these challenges (Goetz and Dubayah, 2011). Nevertheless, current BIO maps (e.g., Kellndorfer et al, 2012;Wilson et al, 2013) proved to be valuable tools for ecologic and natural resource assessments (Berner et al, 2012;Goetz et al, 2014;Krankina et al, 2014).…”
Section: Tree Carbon Stocksmentioning
confidence: 99%